Horizontal motion in elastic response to seasonal loading of rain water in the Amazon Basin and monsoon water in Southeast Asia observed by GPS and inferred from GRACE. Issue 23 (4th December 2013) - Fu, Yuning; Argus, Donald F.; Freymueller, Jeffrey T.; Heflin, Michael B.
Abstract [1] We find seasonal horizontal crustal motions observed by GPS positioning in elastic response to heavy rainfall in the Amazon Basin and to monsoons in Southeast Asia to be consistent with those inferred from Gravity Recovery and Climate Experiment (GRACE) gravity observations of water mass loading. Solid Earth moves toward the Amazon during heavy spring rainfall and toward Southeast Asia during summer monsoons and back away from these areas 6 months later when the water load is minimum. Vertical oscillations observed by GPS and inferred from GRACE are 2 to 3 times larger than horizontal oscillation near the margins of the areas of large mass loading. Some discrepancies between GPS and GRACE are probably caused by local effects that influence GPS measurements, because the GPS sites that show significant discrepancies also do not match nearby GPS sites. However, when the load is short wavelength, the limited spatial resolution of GRACE can cause systematic misfits.